Dryland swim training - Read, P.
In conclusion dryland training is an important part to a swimmers training routine. Not only does it fine-tune the elite athlete but it can also motivate the junior athlete and keep them in the sport. The combination of dryland training techniques used by a coach will always remain personal preference, but the intensity and technique with which the activities are done will determine the success of the athlete. Injury can be prevented by the simple approach of progression which all of the reviewed articles encouraged. The dryland training of swimmers is a worthwhile activity.